2000
DOI: 10.1091/mbc.11.9.3219
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Podocalyxin Inhibits Cell–Cell Adhesion and Modifies Junctional Properties in Madin-Darby Canine Kidney Cells

Abstract: Podocalyxin is a major membrane protein of the glomerular epithelium and is thought to be involved in maintenance of the architecture of the foot processes and filtration slits characteristic of this unique epithelium by virtue of its high negative charge. However, until now there has been no direct evidence for podocalyxin's function. Podocalyxin is a type 1 transmembrane sialoprotein with an N-terminal mucin-like domain. To assess its function, we cloned rat podocalyxin and examined the effects of its expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
182
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(200 citation statements)
references
References 46 publications
11
182
0
7
Order By: Relevance
“…61 Previously we showed that expression of podocalyxin, another podocyte protein that associates with actin and maintains the filtration slits open in glomeruli, inhibits cell-cell adhesion and decreases TER in MDCK cells. 62 Our finding that nephrin associates with ZO-1 in MDCK-nephrin cells may explain the effects of nephrin expression on the properties of tight junctions because ZO-1 localizes to the cytoplasmic surface of tight junctions and serves as the major scaffolding protein for tight junction strands. 12,13 In conclusion, we show here that nephrin is a component of a large protein complex composed of cell adhesion receptors and cytosolic scaffolding proteins that connect the complex to the actin cytoskeleton and to signaling networks.…”
Section: Discussionmentioning
confidence: 77%
“…61 Previously we showed that expression of podocalyxin, another podocyte protein that associates with actin and maintains the filtration slits open in glomeruli, inhibits cell-cell adhesion and decreases TER in MDCK cells. 62 Our finding that nephrin associates with ZO-1 in MDCK-nephrin cells may explain the effects of nephrin expression on the properties of tight junctions because ZO-1 localizes to the cytoplasmic surface of tight junctions and serves as the major scaffolding protein for tight junction strands. 12,13 In conclusion, we show here that nephrin is a component of a large protein complex composed of cell adhesion receptors and cytosolic scaffolding proteins that connect the complex to the actin cytoskeleton and to signaling networks.…”
Section: Discussionmentioning
confidence: 77%
“…Mice lacking podocalyxin (podx1 Ϫ/Ϫ ) die soon after birth with defective kidney development and anuria (18) consistent with podocalyxin acting as an antiadhesin on the podocyte surface to ensure filtration slits remain patent. The importance of glycosylation in podocalyxin function is highlighted by the removal of sialic acid, which has been shown to affect cell adhesion and junctional permeability (19). Because plt1͞plt1 mice are able to produce urine, hypoglycosylated podocalyxin appears sufficient for at least partial renal function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the podocytes of the kidney glomerulus, PODXL repels cells from one another (37), whereas in vascular endothelial cells, it plays a pro-adhesive role as a ligand for Lselectin (38). These differences in function are likely due to differences in the glycosylation state of the large extracellular domain of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PODXL in normal tissue has been reported as limited to glomerular podocytes, vascular endothelial cells, platelets, hematopoietic stem cells, and mesothelial cells (38,42,43) as well as to prostate tissue. 4 The anti-adhesive function of PODXL in the kidney glomerulus is essential for maintaining the slit diaphragms between podocyte foot processes through which the urine is filtered (37). PODXL Ϫ/Ϫ mice die soon after birth due to anuric renal failure (44).…”
Section: Discussionmentioning
confidence: 99%